Correction: Spatial organization of the budding yeast genome in the cell nucleus and identification of specific chromatin interactions from multi-chromosome constrained chromatin model. - PLOS Computational Biology Staff (PLoS Computational Biology, 2017)
[This corrects the article DOI: 10.1371/journal.pcbi.1005658.].